İktisat dergilerine göre Osmanlı Devleti’nin iktisadi durumu (1857-1923) - Demir, Kenan (Karadeniz Teknik Üniversitesi Sosyal Bilimler Enstitüsü, 2018)
Bu çalışmada Osmanlı’da yayımlanan iktisadi dergileri tespit edilmiş ve dergilerin içeriği analiz edilmiştir. Osmanlı’da ilk iktisat dergisi 1857 senesinde yayımlanan Ceride-i Ticaret’tir. Bu derginin yayımlanmasından 1923 senesine kadar iktisadi konuları ele alan birçok dergi yayımlanmıştır. İlk dönemlerde iktisadi politikaları doğrudan içeren dergi sayısı azımsanacak miktardadır. Dergiler daha çok ticaret, bayındırlık ve ziraat gibi sektörel olarak yayımlanmıştır. II. Abdülhamit döneminde basında denetimin ağırlaşması nedeniyle iktisat dergileri yayımlanmamasına karşın dönemde çıkan fikir ve edebiyat dergilerindeki iktisadi yazılar azımsanmayacak derecededir. II. Meşrutiyet sonrası basında görülen canlanma iktisadi yayıncılığa da yansımış, bu dönemde birçok iktisadi dergi yayımlanmış, ayrıca fikir dergilerinde de iktisadi konuların içeriği daha fazla olmuştur. Bu dergilerin çoğunluğu belli bir düşünce doğrultusunda yayım yapmaktan ziyade ya güncel iktisadi sorunlara değinmiş ya da halkın iktisadi bilgisi artırmayı hedeflemiştir. Osmanlı’da görülen iktisadi dergilerde ziraat, ticaret, sanayi, kalkınma, mesleki eğitim, bankacılık, borçlanma, mali politikalar şirketleşme, iktisat düşüncesi gibi hemen hemen tüm konularda yazılar görülmüştür.

In this study, the economic magazines published in the Ottoman Empire were identified and the contents of the magazines were analyzed. The first economic magazine in the Ottomans was Ceride-i Ticaret, published in 1857. From the publication of this magazine until 1923, many magazines were published covering economic issues. The number of journals containing direct economic policies in the early periods is a scanty amount. The magazines are mostly published in sectors such as trade, public works and agriculture. Although economic journals were not published due to the aggravation of supervision during the period of Abdülhamit II, the economic literatures in the periodicals and literary journals are not to be underestimated. The revival seen in the post-constitutional period was seen in economic publishing, in which many economic journals were published, and in economic journals, the economic content was more. The majority of the journals published in the Ottomans were aimed at increasing the economic knowledge of the people who had either touched the current economic problems rather than publishing them in a certain way. In economic magazines in the Ottoman Empire, writings on almost all subjects such as agriculture, commerce, industry, development, vocational education, banking, borrowing, financial policies, corporation, economic thought were seen.
Economic situation of the Ottoman Empire according to the economic journals (1857-1923)
Keywords: Osmanlı Devleti; İktisadi Yayıncılık; Ekonomi; The Ottoman Empire; Economic Publishing; Economy